Glycol chitosan-based renal docking biopolymeric nanomicelles for site-specific delivery of the immunosuppressant. (1st August 2020) - Kim, Chang Seong; Mathew, Ansuja Pulickal; Uthaman, Saji; Moon, Myeong Ju; Bae, Eun Hui; Kim, Soo Wan; Park, In-Kyu
Graphical abstract: Highlights: Hydrophobically modified glycol chitosan polymeric nanomicelles (HGC) loaded with hydrophobic drug tacrolimus (TAC). Selective deposition of TAC into the kidney because of the in-built property of glycol chitosan to target the kidney. Megalin receptor-mediated endocytosis is involved in the uptake and retention of HGC-TAC nanomicelles in the kidney. Demonstrates the potential of HGC nanomicelles as a novel strategy to deliver drugs specifically to kidneys without any systemic toxicity. Abstract: In this study, we propose the use of glycol chitosan for the targeted delivery of hydrophobic drugs such as tacrolimus (TAC) towards the kidney. We synthesized a hydrophobically modified glycol chitosan (HGC) polymeric nanomicelle followed by loading TAC resulting in TAC loaded HGC nanomicelles (HGC-TAC). The HGC-TAC nanomicelles displayed spherical morphology with superior drug loading content and encapsulation efficiency. in vitro and in vivo evaluations demonstrated that HGC-TAC nanomicelles are non toxic and delivered TAC preferentially to kidney while lowering the plasma concentrations. The therapeutic effects of HGC-TAC and unencapsulated ("bare") TAC on the kidneys showed that a single intravenous administration of HGC-TAC achieved a therapeutic efficacy comparable to that obtained from daily intraperitoneal injections of TAC for 14 days without any systemic side effects. Thus, HGC-TAC nanomicelles could be effectively used for delivery of TAC towards the kidney, highlighting its potential as a safe modality for renal-targeted delivery of therapeutics.